2018
DOI: 10.1155/2018/8412098
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extracts ofCordyceps kyushuensisKob Induce Apoptosis to Exert Anticancer Activity

Abstract: Cancer has become the leading cause of mortality since 2010 in China. Despite the remarkable advances in cancer therapy, a low survival rate is still a burden to the society. The antineoplastic activity of aqueous extracts of Cordyceps kyushuensis Kob (AECK) was measured in this study. Results showed that AECK can significantly inhibit the proliferation and viability of U937 and K562 when treated with different concentrations of AECK, and the IC50 values of U937 and K562 were 31.23 μg/ml and 62.5 μg/ml, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Complexes of some cordycipitoid fungal species and their natural host, such as C. militaris Fr., C. chanhua Z. Z. Li, F. G. Luan, Hywel-Jones, C. R. Li and S. L. Zhang, and C. kyusyuensis Kawam, have received significant attention in traditional medicine industry due to the detection of bioactive compounds with anti-aging, anti-tumor, antioxidant, anti-inflammatory, and immuno-modulatory effects ( Castillo et al, 2018 ; Zhao et al, 2018 ; Lou et al, 2019 ; Li et al, 2021 ; Zhang et al, 2021 ). Cordyceps tenuipes (Peck) Kepler, B. Shrestha and Spatafora has been applied in a variety of functional foods in Japan and South Korea, possessing nutritional, immune-regulatory, antitumor, analgesic, antibacterial, and anti-malaria effects ( Wang Y. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Complexes of some cordycipitoid fungal species and their natural host, such as C. militaris Fr., C. chanhua Z. Z. Li, F. G. Luan, Hywel-Jones, C. R. Li and S. L. Zhang, and C. kyusyuensis Kawam, have received significant attention in traditional medicine industry due to the detection of bioactive compounds with anti-aging, anti-tumor, antioxidant, anti-inflammatory, and immuno-modulatory effects ( Castillo et al, 2018 ; Zhao et al, 2018 ; Lou et al, 2019 ; Li et al, 2021 ; Zhang et al, 2021 ). Cordyceps tenuipes (Peck) Kepler, B. Shrestha and Spatafora has been applied in a variety of functional foods in Japan and South Korea, possessing nutritional, immune-regulatory, antitumor, analgesic, antibacterial, and anti-malaria effects ( Wang Y. et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The group reported the upregulated amount of Ca 2+ and downregulated expression of Bcl-2, which indicated that AECK triggered intrinsic apoptosis. Meanwhile, AECK gave rise to extrinsic apoptosis via elevating the level of Fas death receptor in U937 cells [60].…”
Section: Both Intrinsic and Extrinsic Apoptotic Pathways Involved In mentioning
confidence: 99%
“…The patented Chinese prescription "Shuangshen granules" (SSG; Radix Notoginseng, Cordyceps and Radix Panacis quinquefolii, Patent Number: 201310091864.4) can be effectively used to prevent tumours and treat cancer, and represents a signi cant development in terms of theory, practice and innovation in the eld of cancer prevention and treatment. Studies have shown that Cordyceps extract can induce apoptosis, arrest the cell cycle in the S phase, and increase endoplasmic reticulum stress to inhibit the proliferation of cancer cells, thus has important 'anti-cancer' roles [17][18]. In addition, Cordycepin, a bioactive component of Cordyceps, can suppress the migration and invasion of human liver cancer cells by downregulating the expression of CXCR4 [19].…”
Section: Introductionmentioning
confidence: 99%